RE-DESIGN DAN PENANGANAN BREAKWATER DI PELABUHAN BATANG - Ari Surya Bawono; Rizki Indianto; Indrastono Dwi Atmanto; Bambang Pardoyo (Jurnal Karya Teknik Sipil, 2014)
Onshore espescially needed a prevention to sea water abration towards the  geomorfology of shore. The Ones of prevention is build a breakwater. Breakwater must be analyst for strong to prevent from sea water  pressure are come from the sea wave. That analyst include condition where on slope occured landslide are make The building collapse. On this analyst is settle The manual analysis of slope stability with  Fellenius method and Plaxis analisys for breakwater on sta 00+350 in Ports of  Batang Districs. Result of this analyst is generate 1.25 < Safety of Factor < 1.4 is determined that The slope stability on breakwater is safe but not stable and The handling solution based on construction is used The bore-pile foundation Ø800mm with depth 24 m from seabed and elevation step construction.